Pengaruh Pemahaman Materi Aqidah Ibadah Terhadap Prilaku Religiusitas Siswa SMK Muhammadiyah Magelang - Widodo, Widodo (Universitas Muhammadiyah Magelang, 2019)
This study aims to determine the understanding of religious aqeedah material of Magelang Muhammadiyah Vocational High School students, the religious behavior of Magelang Muhammadiyah Vocational High School students, and the influence of the understanding of religious aqidah material on religious grade XI students of SMK Muhammadiyah Magelang. The study was conducted at SMK Muhammadiyah Magelang by taking respondents from class XI as many as 45 students from 130 students there. The methods used are quantitative methods, questionnaire methods and simple linear regression data analysis. The results of the study, the influence of understanding of religious aqeedah of students of SMK Muhammadiyah by 100% categorized in high level, behavior of Students of Muhammadiyah Vocational School Magelang which is 84.4% categorized in moderate level, and there are differences in understanding of religious aqidah worship material on the religious behavior of class XI students in Vocational High Schools (SMK) Muhammadiyah Magelang, obtained an F value of 34.4 and sig. of 0.020 which means that there is a significant influence between the variables